Editorial :WiMAX, LTE, and WiFi interworking - Saeed, Rashid Abdelhaleem; Mabrouk, Ahmed A. M. Hassan; Mukherjee, Amitava; Falcone, Francisco; Wong, K. Daniel (Hindawi Publishing Corporation, 2010)
Recently wireless network interworking has become an important area of research in academia and industry. This is due to the huge diversity of wireless network types, which range from wireless body area network (WBAN) covering areas up to a few inches to wireless regional area networks (WRANs) covering up to several miles. All these types of networks have been developed separately with different usage and applications scenarios, which make interworking between them a challenging task. Themain challenges in wireless interworking of connecting the cellular network with the other wireless networks include issues like security, seamless handover, location and emergency services, cooperation, and QoS. The developed interworking mechanisms, that is, unlicensed mobile access (UMA), IP Multimedia Subsystem (IMS), and Media independent handover (MIH), due to the characteristics of wireless channel, need to be analyzed and tested under various circumstances.